2011
DOI: 10.1002/ibd.21562
|View full text |Cite
|
Sign up to set email alerts
|

Pregnane X receptor (PXR/NR1I2) gene haplotypes modulate susceptibility to inflammatory bowel disease

Abstract: Several PXR/NR1I2 haplotypes contribute to CD susceptibility, suggesting a role for PXR in the IBD pathogenesis of a certain patient subcohort. Given the accumulating evidence for an important role of PXR in intestinal inflammation, further analyses are required to investigate the functional and pharmacogenetic implications of these PXR/NR1I2 gene variants in IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 41 publications
(47 reference statements)
1
28
0
Order By: Relevance
“…Our study may provide insight into how PXR dysfunction may contribute to IBD susceptibility (Langmann et al, 2004;Dring et al, 2006;Martinez et al, 2007;Glas et al, 2011). Whereas others have characterized the anti-inflammatory effects of PXR signaling in the gut, our in vitro and in vivo data suggest that selective activation of the PXR affords protection of the intestinal epithelial barrier in the context of inflammation.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our study may provide insight into how PXR dysfunction may contribute to IBD susceptibility (Langmann et al, 2004;Dring et al, 2006;Martinez et al, 2007;Glas et al, 2011). Whereas others have characterized the anti-inflammatory effects of PXR signaling in the gut, our in vitro and in vivo data suggest that selective activation of the PXR affords protection of the intestinal epithelial barrier in the context of inflammation.…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, genetic studies have identified single-nucleotide polymorphisms in NR1I2, the gene that encodes the PXR, which are associated with increased susceptibility for developing Crohn's disease and ulcerative colitis (Langmann et al, 2004;Dring et al, 2006;Martinez et al, 2007;Glas et al, 2011). Furthermore, others have reported that selective activation of the PXR attenuates nuclear factor k-light-chain-enhancer of activated B cells (NFkB)-dependent inflammatory signaling in the intestinal epithelium Mencarelli et al, 2010Mencarelli et al, , 2011, an effect associated with protection in experimental models of colitis Shah et al, 2007;Dou et al, 2012Dou et al, , 2013Terc et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These 71 susceptibility loci explain only slightly more than 20% of CD heritability. Therefore, it is assumed that a number of rare SNPs and haplotypes contribute to the overall CD risk such as recently shown by us for PXR gene variants [58]. In addition, most likely a high number of common CD risk genes with small effect size are still unidentified but for their identification very large cohorts would be required.…”
Section: Discussionmentioning
confidence: 99%
“…An Irish cohort including 422 patients with IBD and 350 ethnically matched controls was examined for single nucleotide polymorphisms (SNPs), and several polymorphisms were identified in the PXR gene that were over-represented in IBD patients as compared with controls 57 . Moreover, an independent study identified other SNPs in the PXR gene that were associated with CD but not with UC in Caucasian patients 58 . Evaluation of a Spanish cohort of 365 UC and 331 CD patients, and 550 ethnically matched controls showed significant differences in the overall haplotype of IBD between UC and CD patients 59 in PXR SNPs.…”
Section: Mechanisms For the Influence Of Pxr On Ibdmentioning
confidence: 99%